G78(P) The Youngest Child with Familial Polyposis Coli. (7th April 2014) - Tseretopoulou, X; Azaz, A
Abstract : Aims: Familial adenomatosous polyposis (FAP) is an autosomal dominant condition characterised of the development of large numbers of colorectal adenomatous polyps. The average age of onset of polyposis is 16 years, with the youngest patient reported in literature diagnosed at the age of 7 years old (Alkhouri et al, J Pediatr Gastroenterol Nutr . 2010). We present the youngest child with FAP whose symptoms started at 2 years of age. Methods: Three years and eight months old girl presented with two years history of rectal bleeding. Full blood count, platelets number, liver function test and coagulation screen were all normal. She has had no family history of bleeding disorder or bowel problems and no symptoms of constipation. Her anal skin was intact. On failing to improve on empirical laxative treatment, she underwent a colonoscopic examination. Results: Colonoscopy showed hundreds of polyps throughout the entire length of the colon suggestive of Familial Polyposis Coli. Histological examination of polyps' specimens indicated features of tubular adenomas with moderate degree of dysplasia. Upper gastrointestinal endoscopy at a later stage revealed no polyps. Congenital hypertrophy of the retinal pigment epithelium of the right fundus was seen on ophthalmological assessment and an odontome was identified on oral examination. Furthermore, she was found to be positive for the APC gene confirming the diagnosis of FAP in her. Both parents were found to be APC gene negative. Accordingly, total colectomy with ileal pouch and ileostomy formation was performed at the age of 4 years and 10 months. The ileostomy was reversed a year later. Apart from frequent bowel motions for which she is on loperamide, she has remained clinically well and growing satisfactorily with her weight and height around the 91 st percentile at the age of 11 years. Conclusions: We believe this is the youngest patient with a confirmed diagnosis of FAP to be reported. Her disease was de novo and showed dysplastic changes at such an early age necessitating radical surgical intervention which has been well tolerat.